Studi Intertekstualitas Al-Qur'an: Hubungan Dengan Ahlul Kitab dan Kitab Samawi - Mustin, Hilgha; Rijal, Tabhan Syamsu; Ghany, Abdul (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Abstract This journal explores the intertextual study of the Qur’an in relation to previous divine scriptures such as the Torah, Psalms, and Gospel, as well as its broader theological and social connections with the People of the Book, namely Jews and Christians. Employing a qualitative approach through library research, the study aims to uncover the historical and doctrinal continuity between the Qur’an and prior revelations. The Qur’an not only acknowledges the legitimacy of earlier scriptures but also offers corrections for distortions and completes the moral and theological teachings therein. Furthermore, the journal discusses how the Qur’an presents a balanced view of the People of the Book—recognizing their faith and spiritual heritage while also offering constructive critique. The findings highlight that intertextual analysis can serve as an effective tool for fostering inclusive, respectful, and theologically grounded interfaith dialogue. By identifying common ground in the messages of the revealed scriptures, intertextuality becomes a vital instrument for promoting social harmony, strengthening religious tolerance, and bridging divisions in pluralistic societies.